The end of art - Khelifa MAHMOUDI; Wahid BELAKHDAR (Pensées Genre, Penser Autrement)
This study examines the end of art, focusing on the trivialization that has impacted art in the contemporary period, influenced by various challenges faced by modern society, including social media. This raises concerns about the possible end of art. In the current era, art is no longer purely an emotional expression. Instead, it has become intertwined with market demand and supply. Artworks are treated as commodities, and the artist has assumed the role of a craftsman. As a result, there has been a shift from focusing on the substance of art to prioritizing spectacle, leading to a crisis of triviality. Today, individuals lacking true artistic depth are often labeled as artists. This makes it essential to redefine art and determine whether every creation should be considered a genuine work of art. Furthermore, it is crucial to explore the reasons behind the current superficiality in art. The vulgarity that has infiltrated contemporary art, largely due to liberalism and the shallow tendencies of certain individuals, signals the potential end of art in its original form. This study questions whether the end of art is inevitable in light of this decline in quality and substance. Is it possible for art to maintain its relevance and authenticity amidst this growing vulgarity?